2020
DOI: 10.1101/2020.10.06.20207514
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plasma ACE2 activity is persistently elevated following SARS-CoV-2 infection: implications for COVID-19 pathogenesis and consequences

Abstract: COVID-19 causes persistent endothelial inflammation, lung and cardiovascular complications. SARS-CoV-2 utilises the catalytic site of full-length membrane-bound angiotensin converting enzyme 2 (ACE2) for cell entry causing downregulation of tissue ACE2. We reported downregulation of cardiac ACE2 is associated with increased plasma ACE2 activity. In this prospective observational study in recovered COVID-19 patients, we hypothesised that SARS-CoV-2 infection would be associated with shedding of ACE2 from cell m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 8 publications
4
46
4
Order By: Relevance
“…Shedding was the proposed mechanism behind high plasma ACE2 activity after COVID-19 (34), and virus-induced shedding of ACE2 has previously been demonstrated in several studies of SARS-CoV (14-16, 39). Shedding of ACE2 in airway epithelial cells occurs constitutively but is also inducible (6, 14, 16, 40).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Shedding was the proposed mechanism behind high plasma ACE2 activity after COVID-19 (34), and virus-induced shedding of ACE2 has previously been demonstrated in several studies of SARS-CoV (14-16, 39). Shedding of ACE2 in airway epithelial cells occurs constitutively but is also inducible (6, 14, 16, 40).…”
Section: Discussionmentioning
confidence: 90%
“…Male sex deviated from this pattern, with clearly higher sACE2 levels in men than in women. The study by Patel et al and two studies of heart failure also found higher circulating sACE2 antigen/activity in men as compared to in women (34, 46, 47) suggesting that ACE2 shedding may be higher in men under pathological conditions. It warrants further investigation if increased shedding or high sACE2 levels contribute to more severe disease in men.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Recent studies showed increased levels of angiotensin-converting enzyme 2 (ACE2) following SARS-CoV-2 infection (Patel et al ., 2021), and a case report showed very high ACE2 levels in a critically ill COVID-19 patient (Nagy et al ., 2021). ACE2 is a common binding site for both SARS-CoV and SARS-CoV-2 (Zhu et al ., 2018, Hoffmann et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Plasma ACE2 activity is elevated in patients after COVID-19 infection compared to healthy controls. 14 Further, ACE2 plasma concentrations have been measured in patients with risk factors for severe COVID-19 disease. In patients with heart failure, plasma levels of ACE2 were higher in men than in women which could explain the higher incidence and fatality rate of COVID-19 in men.…”
Section: Introductionmentioning
confidence: 99%